Precision and Madness : Swiss Art from Hodler to Hirschhorn - Brüderlin, Markus; Gamper, Michael; Heller, Martin; Schindhelm, Michael; Wallner, Julia; Wechsler, Max; Wyss, Beat; Kunstmuseum Wolfsburg, Wolfsburg (Wolfsburg : Kunstmuseum Wolfsburg, 2007)
Anker, Albert ; Armleder, John M ; Bächli, Silvia ; Ben ; van den Berg, Christoph ; Bill, Max ; Büchel, Christoph ; Burkhard, Balthasar ; Calamé, Alexandre ; Disler, Martin ; Federle, Helmut ; Fischli & Weiss ; Fleury, Sylvie ; Gertsch, Franz ; Giacometti, Alberto ; Hattan, Eric ; Herzog & de Meuron ; Hirschhorn, Thomas ; Hodler, Ferdinand ; Hofmann, Hanspeter ; Klee, Paul ; Lenzlinger, Jörg ; Leutenegger, Zilla ; Lohse, Richard Paul ; Lüscher, Ingeborg ; Lüthi, Urs ; Müller, Robert ; Netzhammer, Yves ; Odermatt, Arnold ; Raetz, Markus ; Rist, Pipilotti ; Rondinone, Ugo ; Roth, Dieter ; Schiess, Adrian ; Signer, Roman ; Soutter, Louis ; Steiner, Gerda ; Streuli, Beat ; Studer, Monica ; Villiger, Hannah ; Wick, Cecile ; Wölfli, Adolf ; Zaugg, Rémy ; Zünd, Robert
Precision and Madness : Swiss Art from Hodler to Hirschhorn, Kunstmuseum Wolfsburg, Wolfsburg, 2007-07-07. 2007-06-24
boek
Keywords: Zwitserland